Rheological Evaluation of Soil Mechanical Stability During Vegetation Restoration - WANG Xinyu; ZHOU Lin; MENG Jing; HU Shaojie; LÜ Yinyan; XU Chenyang; HU Feinan (Shuitu Baochi Xuebao)
[Objective] This study is aiming to evaluate the dynamic evolution of soil microstructure stability during vegetation restoration on the Loess Plateau. [Methods] Soil samples from four stages of vegetation succession in the Ziwuling forest region were examined. Utilizing the amplitude sweep test method, soil shear strength and viscoelastic parameters were assessed under various matric potentials (0, -3 and -10 kPa). Correlation analyses between these parameters and soil physicochemical properties were conducted. [Results] (1) Soil shear strength and viscoelasticity exhibited an increasing trend with advancing vegetation succession stages, attributed primarily to the increasing of soil organic carbon, exchangeable Ca2+ and sand content, along with reduced Na+ during vegetation recovery. This augmentation contributed to enhanced interparticle adhesion and frictional forces. (2) The soil shear strength parameter increased with the decreasing of matric potential. Under low matric potential conditions, there was no significant correlation between soil shear strength parameters (G′LVE、τLVE and τmax) and exchangeable Ca2+ and sand content. Under high matric potential conditions, soil shear strength parameters showed a significant positive correlation with exchangeable Ca2+ (p<0.05), while τmax, G′LVE, τYP, and G′YP exhibited significant positive correlations with sand content. (3) Soil viscoelastic parameters (γYP and Iz) showed a decreasing trend with declining matric potential. Particularly, under high matric potential conditions, these parameters exhibited a positive correlation with organic carbon content, which gradually attenuated with the decreasing of matrix potential. Viscoelastic parameters were negatively correlated with clay content under different matric potentials. (4) The overall mechanical stability of soil was positively correlated with soil Ca2+ at 0 kPa, negatively correlated with soil silt and K+ content at -3 kPa, and positively correlated with clay content at -10 kPa. [Conclusion] The changes and influencing mechanism of soil mechanical stability under different vegetation types and different matric potentials were revealed, which provided an important basis for understanding the evolution of soil characteristics in the process of vegetation restoration on the Loess Plateau, and also provided theoretical support for soil protection and ecological restoration in the future.